Bug Scouts. Out in the wild! - Lowery, Mike, 1980- (Graphix chapters., 2022)
Doug, Abby, and Josh are a part of the Bug Scouts, and while Doug and Abby love everything about it, Josh is less than enthusiastic about being a part of the troop. Luna joins their group, and the scouts set out to earn the "foraging" bug badge, which they can only get if they successfully find an edible plant. They embark on a mission to find a suitable plant while trying to avoid the poisonous ones and a hungry frog.